Mixoid liposarcoma in abdominal wall. Case presentation - Cristina Ruesca Domínguez; Yovanny Ferrer Lozano; Juan Carlos Rodríguez; Maria Elena Medina González (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
The case of a 22 year-old patient is presented, with antecedents of having been operated of subcutaneous lypoma in superior hemiabdomen, that goes to consultation worried by a considerable increase of volume, below the old scar. After carrying out physical exam, ultrasound, and on-line axial computarized tomography, it was decided to proceed to the excerecis whose result was a macroscopic block of solid tissue, yellowish and with abundant mucous secretion, confirmed as a myxoid lyposarcoma .